a=(9-7)(9-4a)

Simple and best practice solution for a=(9-7)(9-4a) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for a=(9-7)(9-4a) equation:


Simplifying
a = (9 + -7)(9 + -4a)

Combine like terms: 9 + -7 = 2
a = (2)(9 + -4a)
a = (9 * 2 + -4a * 2)
a = (18 + -8a)

Solving
a = 18 + -8a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '8a' to each side of the equation.
a + 8a = 18 + -8a + 8a

Combine like terms: a + 8a = 9a
9a = 18 + -8a + 8a

Combine like terms: -8a + 8a = 0
9a = 18 + 0
9a = 18

Divide each side by '9'.
a = 2

Simplifying
a = 2

See similar equations:

| 2.4f=21.6 | | 22b=176 | | 13-2x=12x-13 | | 3(3.666+-1)=8 | | -7d=-84 | | -5(-16x-15)=-8(11+6x) | | y+21=34 | | -8+u=3 | | 3x+62=90+5x | | 67x-3=-3+67x | | 27.5+2= | | 8-3x=2x-3 | | 4x^2-7x+5=-2x+4 | | n-2+1=15 | | 63x+28=-26+63x | | 46x^2+50x-12.5=0 | | 3w+6=36-6 | | 3(n-1)=12 | | .2b=16 | | x*2+46=5*x-11 | | -6x-8+8x=-7x+4 | | 75=x*2.51x | | 2(3x-5)=7x+1 | | 1x+8y=38.5 | | 5x+6-2x=-6+x | | x^2-9x-41=-3x-1 | | 8x+6+2(4x-7)= | | 13-2x=2x-3 | | -7x+9=-8x-3 | | 13x^2+6x-4=0 | | 200=x*2x | | 3t+4=t+-3 |

Equations solver categories